Análise estrutural e aspectos do mosaico sucessional de uma floresta semidecídua em Botucatu, SP - Fonseca, Renata Cristina Batista [UNESP]; Rodrigues, Ricardo Ribeiro [UNESP] (My University, 2000)
The objective of the present paper was to study the structure of a semi-deciduous forest. The main purpose was to verify if the floristic composition and/or structure is influenced by the mosaic developmental phase. The study has been done in 200 plots, each one measuring 10 × 10 m, forming a grid of 200m × 100 m in the center of the forest fragment. In to separate the study area in units representing different phases of forest mosaic (gap, construction and mature), the plots were classified by cluster analysis based on structural traits. The species with the highest influence the community structure were Aspidosperma polyneuron, Trichilia claussenii and Trichilia catigua.Gap, construction and mature phases presented different patterns in spite of the three species influence.
Structural analysis and aspects of the successional mosaic of a semi-deciduous forest, in Botucatu (São Paulo State, Brazil)
Keywords: Floristic; Forest mosaic; Phytosociology; Semi-deciduous forest; Structural analysis; Plants (botany); Semi-deciduous forests; Forestry; Hardwoods; Trichilia